Height development and multiple bone health indicators in children aged 2-12 years with Duchenne muscular dystrophy (DMD). - Bingying Wang; Linyuhan Zhou; Shuangru Li; Huayan Xu; Yingkun Guo; Qin Hu; Min Huang; Dan Zhou; Xiaotang Cai; Qiu Wang; Xiaomei Sun (PLoS ONE)
Introduction Short stature is a frequent complication of DMD, and its pathomechanisms and influencing factors are specific to this disease and the idiosyncratic treatment for DMD. Purpose To establish the height growth curve of early DMD, and evaluate the potential influencing markers on height growth, provide further evidence for pathological mechanism, height growth management and bone health in DMD. Methods A retrospective, cross-sectional study of 348 participants with DMD aged 2-12 years was conducted at West China Second Hospital of Sichuan University from January 2023 to October 2023. Results The growth curve for 2-12 years old boys with DMD indicates a slower growth rate compared to the average population. At age two, children with DMD have a similar height to their peers, but gradually falls behind afterwards. Short stature was observed in children with DMD before and after GC exposure, and prolonged GC use exacerbated the retardation. BMI (β = -0.47, p = 0.007), BMD (β = -0.005, p = 0.014), β-CTX (β = 0.001, p = 0.002), delayed BA (β = 0.417, p < .001), GC duration (β = -0.006, p = 0.047) were independent influencing factors of height. Relevant bone health markers showed different sequential changing patterns. Conclusion The high proportion and progression of short stature are associated with the broad bone health status. Different bone indicators have different sensitivities and specificities and need to be considered together for clinical monitoring of bone health. This study provides evidence for the early monitoring of height development and relevant factors as part of bone health management in DMD, to minimize the occurrence of bone-related complications later in life.